LEARNING EFECTIVENESS USING THEPROJECT BASED LEARNING (PjBL) MODEL INELEMENTARY SCHOOLS - Shakila Oktaviani; Riski Mariska (CV Grasta Glory, 2025)
This model emphasizes students working together to address a problem, ultimately esulting in the development of a product that showcases their abilities. The approach employed in this study is a systematic literature review (SLR). The research involved gathering various articles connected to the effect of the PjBL model in elementary school education. The literature study was carried out on national journal articles indexed by SINTA which were accessed through google scholar with a publication time span of the last 4 years. The results obtained stated that the PjBL model was effective for teaching in elementary schools where the PjBL model was declared effective in stimulating critical thinking skills in students and increasing learning motivation, besides that it was also useful for increasing learning interest and learning result of elementary school students.